2012
DOI: 10.1007/s00018-012-0955-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A binds to αvβ6-integrin and promotes wound healing in mice

Abstract: Chromogranin A (CgA), a secretory protein expressed by many neuroendocrine cells, neurons, cardiomyocytes, and keratinocytes, is the precursor of various peptides that regulate the carbohydrate/lipid metabolism and the cardiovascular system. We have found that CgA, locally administered to injured mice, can accelerate keratinocyte proliferation and wound healing. This biological activity was abolished by the Asp(45)Glu mutation. CgA and its N-terminal fragments, but not the corresponding Asp(45)Glu mutants, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The first indication of a defined receptor for the fulllength CgA and its N-terminal fragment vasostatin-1 stems from a recent study on wound healing in injured mice [64]. A selective binding of CgA and vasostatin-1 to integrin avb6 was demonstrated in the low nanomolar range.…”
Section: Putative Receptors and Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first indication of a defined receptor for the fulllength CgA and its N-terminal fragment vasostatin-1 stems from a recent study on wound healing in injured mice [64]. A selective binding of CgA and vasostatin-1 to integrin avb6 was demonstrated in the low nanomolar range.…”
Section: Putative Receptors and Mechanismsmentioning
confidence: 99%
“…No binding has been observed, to other RGD-dependent and -independent integrins, such as avß3, avß5, avß8, a5ß1, a1ß1, a3ß1, a6ß4, a6ß7 and a9ß1, in the low nanomolar range. However, it is noteworthy that various peptides of different length containing the integrin-binding region of vasostatin-1 could recognize, in the low micromolar range, also the integrin avß3 [64]. For example, in competitive binding assays the peptide CgA 39-63 could bind avß3 and avß6 with a Ki of 1.7 lM and 7 nM, respectively.…”
Section: Putative Receptors and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…CgA is also expressed in lower amounts by granulocytes, cardiomyocytes and, in certain conditions, by keratinocyte [1, 3-5]. An increasing number of studies have shown that CgA and certain CgA-derived peptides, called vasostatin-1, pancreastatin, catestatin and serpinin, can regulate the cardiovascular system and metabolism, suggesting that this protein can exert extra-cellular functions [1].…”
Section: Introductionmentioning
confidence: 99%